Strengthening Religious Moderation Literacy For Muhammadiyah Citizens, In The Leaders Of The Muhammadiyah Branch, Medan City, North Sumatera Indonesia - Hasanuddin; Nurman Ginting (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Moderate Islam is a teaching that is able to keep up with the times and doesnot leave the teachings after it. But now, most people consider moderateIslam as a liberal or deviant teaching. Therefore, Muslims are calledummatan washatan, harmonious and balanced people, because they areable to combine the two poles of the previous religion, namely Judaismwhich is too down to earth and Christianity which is too high. Theunderstanding of moderate Islamic values is currently starting to be erodedby changing times, so that many people misunderstand moderate Islamwhich is considered a compromise of religious theological beliefs withadherents of other religions, so that people perceive moderation as aliberal attitude, and raise public antipathy in dealing with religiousmoderation. Moderation Literacy referred to in this service activity isreinforcing the importance of understanding related to religiousmoderation for Muhammadiyah organization cadres at the MuhammadiyahBinjai Branch Leadership. This activity of strengthening religiousmoderation literacy is carried out by training methods by presentingvarious materials related to religious moderation that are oriented toMuhammadiyah ideological texts.